Beckett et les mots de l’affect - Lis, Jerzy (Wydawnictwo Naukowe UAM, 2003)
The subject o f this article is analysis o f Beckett’s affective language in his play Comment c ’est. The author shows similarity o f many o f the playwrights procedures to Ludwig Wittgenstein’s philosophical conceptions.